2005
DOI: 10.1590/s0100-29452005000200018
|View full text |Cite
|
Sign up to set email alerts
|

Rendimento e qualidade da fruta do maracujazeiro-amarelo adubado com potássio, esterco de frango e de ovino

Abstract: A maioria dos solos cultivados com maracujazeiro no Estado de Sergipe é de baixa fertilidade natural, o que tem ocasionado reduzida produtividade desta fruteira. Assim, objetivou-se avaliar a combinação de fontes de adubos orgânicos, esterco de frango e de ovino, às doses de potássio no rendimento e na qualidade das frutas do maracujazeiro-amarelo. O experimento foi realizado no Câmpus Rural da Universidade Federal de Sergipe. O delineamento experimental foi em blocos ao acaso, em esquema fatorial [(2x5)+1], c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 4 publications
(3 reference statements)
0
4
0
5
Order By: Relevance
“…BRITO et al (2005) encontraram diferenças na espessura da casca de frutos de maracujazeiro utilizando tratamentos com diferentes fontes e doses de adubos orgânicos, indicando que esta característica está diretamente ligada aos fatores nutricionais.…”
Section: Resultsunclassified
“…BRITO et al (2005) encontraram diferenças na espessura da casca de frutos de maracujazeiro utilizando tratamentos com diferentes fontes e doses de adubos orgânicos, indicando que esta característica está diretamente ligada aos fatores nutricionais.…”
Section: Resultsunclassified
“…The application of potassium chloride with cattle manure contributed to the increase in solid soluble contents of noni fruits due to the induction of synthesis and translocation of carbohydrates and activation of enzymes. It also contributed to the formation of organic acids, which was also found for yellow passion and melon fruits (Brito et al, 2005;Jifon and Lester, 2009). Even considering the soluble solid contents in the fruits, the values were lower than all values obtained by Kumar e Ponnuswami (2013) in fruits of noni under different irrigation regimes and sources of organic manure, which ranged from 7.21 to 10.53°Brix.…”
Section: Resultsmentioning
confidence: 65%
“…In soil fertilization, the use of organic materials added to mineral fertilizers, which significantly influence the root system architecture and the nutritional stage is crucial to the success of fruit production (Brito et al, 2005), for the application of organic sources and mineral fertilization influence on fruit quality of passion fruit plants. However, has little information about the effect of the organic and mineral fertilization on the physical and physicochemical quality noni fruit.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results in this study are similar to those observed by Cobra (2015), when working in the same study area, where the averages ranged from (6.7mm) to (12.2mm), and Figueiredo et al (2015) that obtained values between (7.48mm) to (9.53mm). Brito et al (2005) in studies using treatments with different sources, and doses of organic fertilizers in passion fruit registered differences in the peel thickness evidencing that this characteristic is directly linked to nutritional factors.…”
Section: Resultsmentioning
confidence: 95%